Parafibromin expression in breast cancer: a novel marker for prognostication?. Issue 1 (27th April 2007) - Selvarajan, S; Sii, L-H; Lee, A; Yip, G; Bay, B-H; Tan, M-H; Teh, B-T; Tan, P-H
Abstract : Background: Parafibromin is a novel protein product of HRPT2, a recently identified tumour suppressor gene. Mutations of the HRPT2 gene are common in parathyroid carcinomas, and these exhibit reduced protein expression. Parafibromin expression in breast cancer has not been previously studied. Aims: To determine the distribution of parafibromin in breast cancer tissues, and correlate its expression with conventional pathological parameters. Methods: Tissue microarrays were constructed from archival paraffin embedded breast cancer samples. Sections cut from tissue microarray blocks were subjected to immunohistochemistry. Immunopositivity for parafibromin and intensity-percentage scores were derived by blinded evaluation. Findings were correlated with clinicopathological parameters. Results: 163 breast cancers were assessed. Larger tumours were less likely to express parafibromin than smaller ones, with the association approaching statistical significance (p = 0.05). Staining intensity correlated inversely with tumour size (p = 0.016) and pathological stage (p = 0.008); as did parafibromin intensity-percentage score with pathological stage (p = 0.03), lymphovascular invasion (p = 0.03) and cerbB2 intensity-percentage score (p = 0.04). Conclusion: Parafibromin in breast cancer, as in parathyroid tumours, appears to have tumour suppressor functions, with loss of protein expression associated with adverse pathological parameters. These findings may indicate a potential role of parafibromin as a prognostic marker in breast cancer.